Allosteric control of transcription in GntR family of transcription regulators: A structural overview. Issue 7 (14th July 2015) - Jain, Deepti; Salunke, Dinakar M.
Abstract The GntR family of transcription regulators constitutes one of the most abundant family of transcription factors. These modulators are involved in a variety of mechanisms controlling various metabolic processes. GntR family members are typically two domain proteins with a smaller N‐terminus domain (NTD) with conserved architecture of winged‐helix‐turn‐helix (wHTH) for DNA binding and a larger C‐terminus domain (CTD) or the effector binding domain which is also involved in oligomerization. Interestingly, the CTD shows structural heterogeneity depending upon the type of effector molecule that it binds and displays structural homology to various classes of proteins. Binding of the effector molecule to the CTD brings about a conformational change in the transcription factor such that its affinity for its cognate DNA sequence is altered. This review summarizes the structural information available on the members of GntR family and discusses the common features of the DNA binding and operator recognition within the family. The variation in the allosteric mechanism employed by the members of this family is also discussed. © 2015 IUBMB Life, 67(7):556–563, 2015